L’uso delle costruzioni marcate nel teacher talk dell’insegnante di italiano L2 del Belgio francofono - Greco, Alessandro (Incontri. Rivista europea di studi italiani, 2022)
The use of marked structures in the teacher talk of the Italian as L2 teacher in Francophone BelgiumThe aim of this article is to present and discuss the first results of a research study on the teacher talk (TT) for Italian as foreign language (IL2) teachers in Belgium. In particular, data from the pilot corpus of the study, conducted in the French-speaking area of the country, are analysed. The TT is examined from a morphosyntactic point of view, in order to track the presence or absence of some spoken features typical of neo-standard Italian: the marked constructions, i.e. structures that present modifications of the canonical order of the subject-verb-object (SVO) elements, to respond to pragmatic communication goals. TT features could be an indicator of the structure and specificity of the teachers' spoken Italian, and at the same time provide information on their linguistic and cultural identity. IL2 teachers in Francophone Belgium are in fact mostly of Italian origin. This suggests that their TT is probably influenced by their socio-biographic profile as well as their linguistic repertoire.